Tax competitiveness of the new EU member states - Askoldas Podviezko; Lyudmila Parfenova; Andrey Pugachev (Journal of Risk and Financial Management, 2019)
This paper investigates tax competitiveness among the EU member countries. The tax competition of countries causes both positive and negative effects on macroeconomic processes such as the effectiveness of government spending, the rationality of supply of externalities, and the length and amplitudes of business cycles. A considerable reduction of corporate tax in the EU is related to increased tax competition after new members entered the EU. Multiple criteria methods were chosen for the quantitative evaluation of EU countries from different regions of the EU. Criteria of evaluation were chosen and structured into a hierarchy. The convergence process of the new members of the EU is reinforced with the increasing tax competitiveness of such countries. Results of the multiple criteria evaluation revealed both the factors that increased the tax competitiveness of new members of the EU, and outlined the factors that hampered such competition.
Keywords: 330; state tax risks; loss of competitiveness of tax system; tax competition; tax revenues; tax burden; multiple criteria evaluation; PROMETHEE